MENINGKATKAN RESILIENSI REMAJA MELALUI BIBLIOCOUNSELING - Sholih -; Rochani -; Deasy Yunika Khairun; Ibrahim Alhakim (Jurnal Penelitian Bimbingan dan Konseling, 2017)
The aim of the present study was to examine the effectiveness of resilience with students of groupB in PKBM Kencana Ungu. The study posses equivalent time series quasi experimental design. The data was analyzed by using analysis of varians or ANOVA to identify the significance resilience enhance. The result provide an evidance  that bibliocounseling was effective to enhance resilience of students who was studied. Keywords: effectiveness, time series, exploration stage of career maturity, career guidance.